The correlation between the use of personal protective equipment and level wild-type p53 of dental technicians in Surabaya - Puspa Dila Rohmaniar; Titiek Berniyanti; Retno Pudji Rahayu (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Exposure of metals among dental technicians that come from the working environment can lead to the formation reactive oxygen species (ROS). ROS can cause mutations in the p53 gene (p53). The mutation is transversion mutation GuanineThymine. p53 mutations can lead to low expression of the wild-type p53 protein (p53). Wild-type p53 involved in many biological processes such as regulation of genes involved in cell cycle, cell growth after DNA damage, and apoptosis. However, exposure to metals among dental technicians can be prevented through the use of personal protective equipment (PPE) during work. Purpose: The purpose of this study was to analyze the correlation between the use of personal protective equipment to wild-type p53 protein levels among dental technicians in Surabaya. Method: This study was observational analytic with cross sectional approach. 40 samples were taken by random sampling. Data were retrieved through interviews and observations. Wild-type p53 was analyzed from saliva with indirect ELISA method. Analysis of data used Kolmogorov Smirnov normality test and a Pearson correlation test. Value significance was p<0.05 (95% confidence level). Result: There was a significant association between the use of personal protective equipment with wild-type p53 levels with p=0.002 Conclusion: The use PPE properly is positively correlated with the wild-type p53 protein levels of dental technicians in Surabaya.